2020
DOI: 10.3389/fneur.2020.00728
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and Hemorrhagic Transformation After Endovascular Therapy for Ischemic Stroke

Abstract: Hemorrhagic transformation remains a potentially catastrophic complication of reperfusion therapies for the treatment of large-vessel occlusion ischemic stroke. Observational studies have found an increased risk of hemorrhagic transformation in patients with elevated blood pressure as well as a high degree of blood pressure variability, suggesting a link between hemodynamics and hemorrhagic transformation. Current society-endorsed guidelines recommend maintaining blood pressure below a fixed threshold of 180/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Figure 3 shows the presence of HT within or above the autoregulatory limits due to fluctuations in blood pressure. This investigation showed that the autoregulatory parameter in the ipsilateral cerebral hemisphere was lower than that in the opposite hemisphere, indicating a decrease in the ability to buffer blood pressure fluctuations ( 91 ). In patients with stroke with cerebral autoregulation impairment, restoration tends to be delayed for up to 3 months, emphasizing the clinical relevance of autoregulation in stroke research ( 109 , 110 ).…”
Section: Blood Pressure Management After Thrombectomy For Preventing Htmentioning
confidence: 96%
See 2 more Smart Citations
“…Figure 3 shows the presence of HT within or above the autoregulatory limits due to fluctuations in blood pressure. This investigation showed that the autoregulatory parameter in the ipsilateral cerebral hemisphere was lower than that in the opposite hemisphere, indicating a decrease in the ability to buffer blood pressure fluctuations ( 91 ). In patients with stroke with cerebral autoregulation impairment, restoration tends to be delayed for up to 3 months, emphasizing the clinical relevance of autoregulation in stroke research ( 109 , 110 ).…”
Section: Blood Pressure Management After Thrombectomy For Preventing Htmentioning
confidence: 96%
“…In patients with spontaneous intracerebral hemorrhage, studies have shown that intensive control of systolic blood pressure is relatively safe to lower to 140 mmHg, but this that measure had no apparent effect compared with the systolic blood pressure target of 180 mmHg ( 90 ). Although the optimal target for blood pressure control in sICH is still unclear, the treatment goal is to supply adequate blood flow to the ischemic area, reduce the pressure on the brain with autoregulation impairment, and eventually reduce the risk of hematoma expansion ( 91 ). However, the effects of BP on hematoma enlargement are for primary intracranial hemorrhage and are independent of those in patients with HT after ischemic stroke.…”
Section: Prevention Of Ht Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review described hemodynamic parameters following recanalization and pointed out the fact that BP targets may be dependent on individual parameters such as autoregulatory limits and BP trajectories. In light of this data, chronic high BP in patients with severe carotid stenosis may not require treatment, whereas an unusual increase in BP may represent a risk of reperfusion injury ( 139 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Although current guidelines suggest that systolic blood pressure (SBP) of 180 mmHg can be used as an effective upper limit, Silverman et al suggest that maintaining blood pressure in an optimized range personalized to each patient may result in decreased occurrence of HT [ 62 ]. Improved stroke outcomes are seen when BP is maintained between 140-180 mmHg [ 13 , 63 ].…”
Section: Hypertension and Systolic Blood Pressure Variabilitymentioning
confidence: 99%